A Reading of the Epistemological Systems of the Arabic Linguistic Terminology - .belazoui, salima (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract : Language is one of the cultural systems that distinguish human beings and scientific communication between nations is a human necessity dictated by the conditions of cognitive friction, and it is natural that the term is not separate from scientific field that produced it, it is characterised and pigmented by its origin language and it affects the language translated to it. So it is shows a deficiency in the term imported by Arabic language after it was previously generate it. Among the most mechanisms used to set the Arabic term are the two mechanisms of translation and Arabization. So can they be considered them as two linguistic cognitive phenomenons or woven cultural? Or does each mechanism have tools and properties to make up and compose the term in general and the linguistic in particular, which differs from the other mechanisms? This article aims and intends to answer all this questions.